A Prototype Microwave System for 3D Brain Stroke Imaging - Tobon Vasquez, Jorge A.; Scapaticci, Rosa; Turvani, Giovanna; Bellizzi, Gennaro; Rodriguez-Duarte, David O.; Joachimowicz, Nadine; Duchêne, Bernard; Tedeschi, Enrico; Casu, Mario R.; Crocco, Lorenzo; Vipiana, Francesca (Sensors (Basel, Switzerland), 2020)
This work focuses on brain stroke imaging via microwave technology. In particular, the open issue of monitoring patients after stroke onset is addressed here in order to provide clinicians with a tool to control the effectiveness of administered therapies during the follow-up period. In this paper, a novel prototype is presented and characterized. The device is based on a low-complexity architecture which makes use of a minimum number of properly positioned and designed antennas placed on a helmet. It exploits a differential imaging approach and provides 3D images of the stroke. Preliminary experiments involving a 3D phantom filled with brain tissue-mimicking liquid confirm the potential of the technology in imaging a spherical target mimicking a stroke of a radius equal to 1.25 cm.